Experience report of active methodology applied in a class of the PET dentistry group: anatomy of the maxillomandibular complex and adjacent structures related to their importance in clinical practice (Research, Society and Development, 2022)
The Tutorial Education Program (PET) of the Dentistry course at the State University of Maringá (UEM) has a teaching project called Pilot Project (PI) in which professors from the Department of Dentistry and other areas of UEM are selected and invited by the group to perform an activity with the help of the PET students. This activity is proposed so that the teacher becomes able to apply active methodologies in their undergraduate classes in order to improve both the teaching and learning process, aiming at the development of students' critical, reflective and analytical thinking. With the advent of the COVID-19 pandemic, the non-continuity of face-to-face activities required an adaptation to the use of digital technologies from a didactic-pedagogical bias. Therefore, the objective of this work is to report the experience of Active Methodology applied in an online class of the PET Dentistry group, whose theme was the "anatomy of the maxillomandibular complex and adjacent structures related to its importance in clinical practice".